2005
DOI: 10.4278/0890-1171-19.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Single-Item Measure of Job Satisfaction

Abstract: These results are consistent with other studies and support the psychometric properties of this single-item overall job satisfaction measure. Limitations of the study and its implications for worksite health promotion are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
265
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(307 citation statements)
references
References 8 publications
7
265
0
6
Order By: Relevance
“…As for subjective complaints, higher scores indicate more frequency of episodes. With regard to job satisfaction which is the main outcome of our study, the validity of a single-item measure has been demonstrated by many studies reported to date [19][20][21][22] . Mental health status was accessed with the 12-item version General Health Questionnaire (GHQ), and through the question about 'whether you are coping effectively with stress (measured by the following scores 1. yes, 2. no)'.…”
Section: Questionnairesmentioning
confidence: 93%
“…As for subjective complaints, higher scores indicate more frequency of episodes. With regard to job satisfaction which is the main outcome of our study, the validity of a single-item measure has been demonstrated by many studies reported to date [19][20][21][22] . Mental health status was accessed with the 12-item version General Health Questionnaire (GHQ), and through the question about 'whether you are coping effectively with stress (measured by the following scores 1. yes, 2. no)'.…”
Section: Questionnairesmentioning
confidence: 93%
“…The participants were asked to rate their work according to their own values, ideals, and purposes from 0 (not at all satisfied) to 5 (satisfied) to 10 (absolutely satisfied). 22 The nurses were also asked to rate their intention to leave from 0 (I definitely think about leaving my job) to 5 (I sometimes think about leaving my job) to 10 (I don't have any intention of leaving my job).…”
Section: Instrumentsmentioning
confidence: 99%
“…If someone wants to measure a CBBE index in an industry with five competitive brands and he or she draws on the OBE model with the four indicator questions, then the number of questions is four times higher than that of the suggested BE_AB model. This overload of questions is likely to lead to problematic responses while at the same time decreasing the validity of the results (Dolbier et al, 2005;Stanton, Sinar, Balzer, & Smith, 2002). If this issue is ignored, the probability of the results being arbitrary is high despite the use of validated measurement models.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is particularly important that the measurement model be simple to use and as parsimonious as possible. If not, an empirical survey may become impractical due to the length of the questionnaire, which is likely to lead to unanswered or rather arbitrarily answered questions, both of which will reduce the validity of the results (Dolbier, Webster, McCalister, Mallon, & Steinhardt, 2005). For the sake of practicality, this report suggests a new easy-to-use and easyto-understand CBBE single-item measurement model that is as valid as already approved models and is thus well applicable for the controlling purposes, especially for practitioners.…”
Section: Introductionmentioning
confidence: 99%